Caracterización de la calidad de agua el río Isinche para el análisis de la descarga en la planta de tratamiento del campus CEASA. - Hidalgo Pio, Daniela Abigail (2024)
The objective of the research work was to evaluate water quality through physical-chemical parameters in order to establish discharge criteria in the water body. The employed methodology consisted of field work, laboratory analysis and the qualitative method use to obtain a general and rapid perception of water characteristics at three sampling points. The results revealed the significant impact of anthropogenic activities on water quality. Analyses showed that pH and electrical conductivity were within the permissible range. In relation to arsenic, a concentration of 0.1471 mg/l was identified at point 1, exceeding the limit for irrigation, but within acceptable margins for livestock use. Only point 1 exceeded the nitrite limit for livestock water, registering 0.428 mg/l, while nitrate levels remained within the permitted limits at all three points. The presence of BOD5 was detected only at point 1, with a value of 3 mg/l. Regarding COD, point 1 presented significantly higher levels (32.8 mg/L) than points 2 and 3, which showed more moderate concentrations (11.1 mg/L and 12.8 mg/L). The negative impact of human activities on water quality in the studied region is evident. In addition, detailed analyses showed contamination levels, with the situation at Hacienda del Niño Isinche standing out. Therefore, the need to implement effective measures to mitigate contamination and protect this vital resource is emphasized.